Enhanced Depth Optical Coherence Tomography Imaging - A Review - Rajendran, Anand; Ramteke, Pushpanjali; Rathinam, SR (Delhi Journal of Ophthalmology, 2014)
The choroid remained till date an unexplored entity due to difficulty in visualization of deeper structures in vivo. The choroid being the vascular inner layer receives maximum blood that flows to the eye. The retina derives its blood supply from the choroid hence any choroidal abnormality ultimately affects the retina. The role of choroid in the pathogenesis of retinal diseases has not been studied in detail. OCT has been a revolution in the field of ocular imaging. Now, Enhanced Depth Imaging Optical Coherence Tomography (EDI OCT), a new investigative modality with its deeper penetration has made the study of the choroid an easy task. Choroidal thickness plays a vital role in the determination of the pathogenesis of various disorders. EDI OCT has been studied in many diseases like myopia, CSCR, DR, ARMD, PCV, age related choroidal atrophy, macular hole and tumors. The exact calculation of choroidal thickness is difficult even in normal eyes as the boundaries of choroid are ill-defined. Measurements are done manually which are subject to interindividual variation. Automated software are still not validated till date. Choroidal thickness varies according to the age, location in relation to the macula and axial length. The choroid is found to be thickest underneath the fovea and thinnest nasally. The choroidal thickness decreases with increasing age and the degree of myopia. Even diurnal variations in choroidal thickness have been extensively studied. Diseases with choroidal hyperpermeability like CSCR, PCV show increased choroidal thickness. Those with chorioretinal atrophy like myopia, macular hole, ARMD, age related choroidal atrophy and inherited retinal dystrophies show reduced choroidal thickness. Choroidal thickness measurement aids in differentiation of ARMD from PCV and CSCR and also has an important role in judging response to different treatment modalities like PDT, lasers and anti VEGF agents. A new terminology age related choroidal atrophy was assigned to those patients with decreased choroidal thickness and without typical features of ARMD. In many of the pathologies not only the affected eye but the fellow eye shows changes suggestive of bilateral nature of these pathologies. Tumors which are posteriorly located and small and undetectable by ultrasonography can be easily visualized with the help of this technique. EDI OCT has a wide variety of implications in the diagnosis of a large number of not only retinal but uveal pathologies too like VKH syndrome. EDI OCT, with improved visualization of deeper retinal tissues and precise measurement of choroidal thickness has enhanced our acumen in the management of many of these pathologies.